Epidemiology and clinical manifestations of COVID-19 during the early outbreak period based on reports from 10 countries - Nadeeka Perera; Sumudu Avanthi Hewage; Nishani Fonseka; Chathurani Wickramaarachchi; Sajani Nadeeka; Hemali Jayasekera; Sachintha Dilhani; Mekala Fernando; Chithramalee Rodrigo; Thirumagal Sivashankar; Nadeeja Liyanage; Samantha Wijewardhane; et al. (College of Community Physicians of Sri Lanka, 2020)
No abstract available